Physical and chemical properties of a sandy loam soil under irrigated rice-wheat sequence in the Indo-Gangetic Plains of South Asia - Gathala, M.K.; Jat, M.L.; Saharawat, Y.S.; Sharma, S.K.; Yadvinder, S.; Ladha, J.K. (OMICS Publishing Group, 2017)
Resource conservation technologies (RCTs) such as zero tillage (ZT), dry direct seeded rice (DSR) and crop residues as mulch are known to increase productivity and profitability of rice-wheat system (RWS) in South Asia. There are, however, few studies on assessing the effect of RCTs on physical and chemical properties of soil under RWS. A field experiment on a sandy loam soil was conducted on RWS for two years at Modipuram, India involving six treatment combinations of three tillage and crop establishment methods in rice, (i) conventional puddled transplanted rice (CT-PTR), (ii) conventional dry tillage followed by direct seeding of rice (CT-DSR), and (iii) zero tillage followed by direct seeding of rice (ZT-DSR), and two green manuring options (with and without intercropping of Sesbania aculeata, -S or +S). In the succeeding wheat, rice residue (RR) was retained in sesbania green manure treatments and it was removed from no sesbania plots. Wheat was direct sown after ZT (DSW) in all the plots. Substituting PTR/ DSW without crop residues with ZT-DSR/DSW plus residue cycling reduced electrical conductivity from 0.146 dS m‒1 to 0.128 dS m‒1 and increased soil organic C from 5.72 g kg-1 to 6.25 g kg-1 in 0-15 cm layer. Similarly, water-stable aggregates (WSAs) >0.25 mm were 28% higher and their mean weight diameter increased by 11.9% in ZT-DSR/ DSW plus residues compared to PTR/DSW without crop residues plots. On average, there was a 23.6% increase in large (4.75-8.00 mm) aggregates and a reduction of 15.8% in finer (0.106‒0.25 mm) aggregates in residue retention treatments over the no-residue treatments. In plots without puddling (ZT-DSR), the infiltration rates were higher (2.97-3.34 mmh-1) than in the CT-PTR (2.41-2.62 mmh-1). Residue retention compared to residue removal not only increased available K contents from 110.5 to 129.2 kg ha-1 but also showed favorable effects on soil matric potential and soil temperature during the wheat season. These beneficial effects on soil quality in just two years after introducing conservation tillage and residue management practices demonstrate potential to improve the long-term productivity and profitability of the RWS. However, the increased rate of infiltration under ZT with residue retention needs new irrigation techniques to minimize the loss of water through percolation during rice season